CONTENT ANALYSIS OF INSTAGRAM @BUKUAKIK: CONSTRUCTING VINTAGE BRAND IMAGE IN THE DIGITAL ERA - Putri Anjelina; Eka Anisa Sari (SOSIOEDUKASI, 2026)
This study aims to analyze how visual and narrative elements on the Instagram account @bukuakik construct a vintage brand image in the digital era. This research employs a qualitative descriptive approach using content analysis as the main method. The data consist of 519 Instagram posts published between January and March 2026. The analysis is based on the Customer-Based Brand Equity (CBBE) theory by Kevin Lane Keller, which includes brand identity, brand meaning (performance and imagery), brand response (judgments and feelings), and brand relationship (resonance).The findings indicate that @bukuakik successfully builds a strong brand image through consistent visual aesthetics and interactive content. The use of earth-tone color palettes, vintage objects, and nostalgic storytelling creates emotional engagement and enhances audience perception. Furthermore, the synergy between the main account and the supporting account (@lifeatbukuakik) strengthens the brand’s authenticity and fosters a sense of community among followers In conclusion, @bukuakik has transformed beyond a conventional bookstore into a digital literacy community that delivers both functional value and emotional resonance. This study highlights the importance of integrating visual consistency and narrative strategies in social media marketing to build a distinctive and memorable brand image in the digital era.